Prediction of embryo survival and live birth rates after cryotransfers of vitrified blastocysts. Issue 5 (May 2021) - Coello, Aila; Nohales, Mar; Meseguer, Marcos; de los Santos, M. José; Remohí, José; Cobo, Ana
Abstract: Research question: Which pre-vitrification parameters are the most predictive of survival and live birth in vitrified–warmed blastocyst transfer cycles? Design: A retrospective study including 11, 936 warmed blastocysts. Pre-vitrification morphological parameters analysed for blastocysts included day of vitrification; blastocyst expansion degree; trophoectoderm grade (A, B and C); and inner cell mass grade (A, B and C). Univariate and multivariate generalized estimating equations models were used to analyse survival, clinical pregnancy and live birth rate. A stepwise regression analysis was conducted to select and classify by order which outcomes were the most predictive. Results: The odds of survival increased almost twice for blastocysts with lower expansion degree (OR 1.92; 95% CI 1.37 to 2.69; P < 0.001) and by about 50% for blastocysts vitrified on day 5 (OR 1.56; 95% CI 1.27 to 1.89; P < 0.001). Multivariate generalized estimating equations model showed that trophectoderm grade followed by the day of vitrification were the most significant predictors of live birth. The odds of live birth increased nearly three times for blastocysts with trophectoderm graded as A compared with those with trophectoderm graded as C (OR 2.85; 95% CI 2.48 to 3.27; P < 0.001), and double for blastocysts vitrified on day 5 compared with those vitrified on day 6 (OR 2.22; 95% CI 1.97 to 2.49; P < 0.001). The odds of live birth also increased in higher expansion degree blastocysts. Conclusions: Blastocysts vitrified on day 5 and those with higher trophoectoderm grade should be given priority when warming.